Every woman's pharmacy : a guide to safe drug use - Rayburn, William F.; Zuspan, Frederick P.;Fitzgerald, Jeanne Tashian (Toronto, Canada : The C.V. Mosby Company, 1983)
This book was written specifically for this purpose, so that the inquiring reader may become more aware of widely available and frequently prescribed medications - their active ingredients, standard dosages, side effects, hazards and benefits - and to be better informed in choosing nonprescription drugs.
1. Nutrition, diet supplements, and nausea medications during pregnancy -- 2. Drug effects on the unborn baby -- 3. Medical disorders and pregnancy -- 4. The pregnant drug abuser -- 5. Pain relief during labor -- 6. Postpartum care -- 7. breast-feeding and drugs -- 8. Birth control pills -- 9. Menstrual irregularities -- 10. menstrual cramps, premenstrual syndrome, and chronic pelvic pain -- 11. Fertility drugs -- 12. Over-the-counter products for women -- 13. Herps and other genital infections -- 14. Drugs for urinary problems -- 15. menopause and estrogen replacement -- 16. Drugs for depression, anxiety, and insomnia -- Appendix.
Includes index.
Keywords: PREGNANCY -- NURSING CARE